Determination of coagulopathy in acute traumatic brain injury and its effect on outcome - Ansari, Safroz; Yadav, Aditya Prakash; Quazi, Masood (Nepal Journal of Neuroscience, 2023)
Introduction: Coagulopathy after traumatic brain injury is quite a common finding. But its role associated with poor outcomes is still debatable. This study was design to assess the frequency, and association of coagulopathy in outcome after TBI. Material and Methods: Single institute prospective study in isolated traumatic head injury was included and outcome was evaluated based Glasgow Outcome Scale recorded at the time of discharge. Coagulopathy was defined as deranged value of aPTT >39s, PT>14s, INR>1.2 and Platelets< 1.5lakhs. Results: Among 405 subjects, mean age of the study population was 28.65 years, majority of the subjects were in the age group of 5-25 years 40.99%, 63.70% were males, mild condition 90.37%, whereas 8.39% presented with moderate and only 1.23% was having severe injury, The mean PT, INR & APTT were 13.69 seconds, 1.1 and 34.50 seconds respectively. The mean platelet count was 261231.9 . Majority of the patients were having good recovery 93.1%, 5.5% had Moderate disability and 1% had severe disability, whereas two patients expired, patients with death and severe disability had higher proportions of coagulopathy, which was also statistically significant coagulopathy. Conclusions: Coagulopathy is significantly associated with unfavorable outcome, though coagulopathy is not an independent factor for poor outcomes in isolated traumatic brain injury.